Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Tanah Datar - Hidayat, Feby; Frinaldi, Aldri; Asnil, Asnil (Sustainability (STPP) Theory, Practice and Policy, 2023)
Regional taxes are mandatory contributions from individuals or entities to the regions in accordance with applicable laws and regulations and are used in running the government with the aim of accelerating development and people's welfare. This study aims to determine the level of contribution of local taxes to PAD. This type of research is descriptive quantitative. The data collection technique used documentation techniques sourced from the 2020-2022 Tanah Datar Regency PAD documents. The results of this study indicate that the contribution of local taxes to PAD in 2020 is 14.57%, in 2021 it is 16.17% and in 2022 it is 17.22%. In general, the contribution of local taxes to PAD has increased every year, but based on the classification criteria, the contribution is included in the less category. The Tanah Datar District Government through the Regional Revenue Management Agency should maximize human resources and infrastructure in maximizing revenue from the local tax sector.